Pilot Survey of Fuel Consumption in Rural Area II - Sagar, S. R.; Chandola, L. P.; Ansari, M. Y. (Indian Forester, 1981)
The pilot studies were carried out to find out the effect of family size and profession of people on consumption of non-commercial fuel e.g., firewood, dung cake and agricultural waste in domestic sector of rural areas. While in villages (in Region I) surrounded by the forests, firewood is the only fuel used in domestic sector, the position is different in Region II where dung cake is also used as fuel and in Region III firewood, dung cake and agricultural waste are found to be used as fuel. The per capita consumption of total fuel in Regions II and III remaining altogether the Same; the firewood, component of non-commercial fuel varies gradually by people belonging to different professions as well as per capita consumption among regions. Thus profession of the people plays a definite role in consumption pattern of non-commercial fuel in domestic sector of rural areas.